Pentingnya Kegiatan Laboratorium (Praktikum) Di Program Studi Pendidikan Fisika Universitas Nacional Timor Lorosae (UNTL) - Maria Lia Felizarda Freitas (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2023)
The objectives of this study include knowing the effect of Laboratory Activities (KL) on the understanding of physics learning concepts; knowing students' understanding of the use of physics lab equipment. This research method is a descriptive qualitative method that describes the opinions and answers of existing participants. The sample of this study was 25 students, who were divided into 5 groups. Each group carried out all the KL that had been prepared. The instruments used in this study were practicum guides, a questionnaire to collect information and opinions from participants according to the questions that had been prepared. The results of the questionnaire analysis showed that the students had very good skills according to their understanding in preparing and assembling equipment for each KL, regarding the language of instruction (Portuguese) used there were some students who requested that the language of instruction used needed to be adjusted to the understanding of students because it was quite difficult for them to understand. The students were successful in implementing KL in the laboratory. The conclusion from the results of this study is that laboratory activities are learning facilities that have a very important role in helping students understand physics theories and concepts well.